Sixth Periodic Monitoring Report on the Status of Implementation Plans in Response to Board-Endorsed IEO Recommendations. (Policy Papers; Policy Paper, 2014)
IMF staff and completed on June 30, 2014 for the Executive Board's consideration on August 7, 2014.